La desigualdad en el acceso a la educación universitaria argentina - Nino, Ezequiel (2011)
The present paper endeavours to tackle (in)equality in Argentina bearing in\nmind the present situation of higher education at state universities. The author analyses\npublic education from the perspective of its alleged levelling function regarding preexisting\ninequalities in society.\nThroughout this paper, the particular characteristics of Argentina's higher education\ninstitutions are revealed, shedding light on the overall unsatisfying situation concerning\nthe supposed equality of opportunities in university spheres. Furthermore, the\nauthor refers to existing studies which show and explain the positive social effects of\naccess to university for underprivileged people, thus highlighting the importance of\ninvestment in higher education